Severe Acute Pulmonary Toxicity Associated with Brentuximab in a Patient with Refractory Hodgkin’s Lymphoma - Yasmin Sabet; Saul Ramirez; Elizabeth Rosell Cespedes; Marimer Rensoli Velasquez; Mateo Porres-Muñoz; Sumit Gaur; Juan B. Figueroa-Casas; Mateo Porres-Aguilar (Case Reports in Pulmonology)
Acute pulmonary toxicity associated with brentuximab appears to be a rare but serious adverse effect that can be potentially fatal. We report the case of a twenty-nine-year-old female with Hodgkin’s lymphoma who was treated with brentuximab and later presented with severe acute pulmonary toxicity; she improved after the discontinuation of brentuximab and administration of antibiotics and glucocorticoid therapy. Currently there is very little data in the literature in regard to the clinical manifestations and characteristics of patients taking brentuximab and the potential development of acute severe pulmonary toxicity, as well as the appropriate therapeutic approach, making this particular case of successful treatment and resolution unique.